(untitled) (Journal of Medical & Health Sciences Review, 2025)
ABSTRACT Background: Lacrimal drainage apparatus produces and drains tears, the balance of which is important for the maintenance of the ocular surface. Congenital anomalies, although rare, are capable of disrupting the dynamics of tears and may lead to clinical conditions like epiphora or dry eye, e.g. supernumerary lacrimal puncta. Such cases, albeit rarely documented, need to be clinically reported for aiding diagnosis and management. Objective :This study aims to document the clinical findings of a patient with a supernumerary lower lid lacrimal punctum and, with the help of the literature, to synthesize its clinical importance, diagnosis, and subsequent effect on the patient’s ocular anatomy and physiology. Methods: The patient was a 56 year old male who was screened for cataract surgery at Al Shifa Trust Eye Hospital, Rawalpindi. He was subject to a host of clinical evaluations, as extensive as slit lamp biomicroscopy and as simple as TBUT. Each finding was analyzed for its association with previously documented cases, following which a narrative literature review was conducted. Findings: The patient presented with two extradistinct puncta on the right lower eyelid: a medial round punctum (0.6 mm) and a lateral slit-like accessory punctum. Probing confirmed separate anatomical openings, while syringing and unable to epilate the punctum yielded punctal regurgitation, alterated contused pliablity regurgitation. TBUT reduced (7 sec R, 9 sec L) although lubricative symptoms in broth occurred. Review Literature (n=52) patients suggest right lower eyelid dominant, with presentations both asymptomatic and symptomatic with tears, dry eye, canaliculitis or conjunctivitis. Conclusion: Supernumerary lacrimal puncta arise from the fusion of the excretory ducts of the lacrimal glands or from the breakdown of a primitive continuum. Resulting drainage abnormalities are often of little clinical consequence, and symptoms are rare. Even in the absence of epiphora, the puncta may be clinically significant and warrant differentiation from anatomical variations of prolapse of the amniotic sac. Comprehensive clinical assessment is fundamental, including the nook and corner parts of the conjunctiva. Dacryocystography might enhance understanding of the anatomy of classified or suspected structural changes. Confirming anatomy helps separate diagnosis from the essential walls of burden and pathology to be overshadowed or complex in epiphora and dry eye to facilitate action.